Toward a collaborative, transformative model of non-profit leadership: Some conceptual building blocks - Bramwell Osula; Eddie C. W. Ng (Administrative Sciences, 2014)
In this paper, the authors propose extending the construct of non-profit leadership to accommodate collaborative and transformational themes. The suggestion is that the resultant broader definition accords with the modern context within which non-profits now operate and feeds into a more resilient model of non-profit leadership. The paper begins with a review of emergent trends in leadership theory and the changing context of the non-profit sector. The argument is made that the extraordinary challenges facing the sector signal the need for fresh new perspectives in leadership. The authors then proceed to examine the significance of a nascent non-profit culture point to a re-alignment of the sector that is informed by transformational principles and a values-orientation. The result is said to be a new model of non-profit and public sector leadership that raises important methodological questions which the authors maintain can inform future analyses of the structure, role, and responsibilities of non-profit leadership. Finally, a world of new possibilities is envisioned, one in which non-profit organizations are strategically repositioned to take advantage of a new values-based ethic that is rooted in principles of integrity, increased self-awareness, a collaborative agenda, intentionality, emphasis of followership, cultural competence, and orientation toward the future.
Keywords: 350; transformational leadership; collaborative leadership; value-based leadership; non-profit; public sector; culture; followers